Investigating the Local Stress of Car Deck Ro-Ro 5000 GT - Alamsyah alamsyah; Ahmed Reza Falevi; Amalia Ika Wulandari; Muhammad Uswah Pawara; Wira Setiawan; Andi Mursyid Nugraha Arifuddin (EPI International Journal of Engineering, 2021)
A deck construction must be strong enough that it will not suffer structural damage if it works under a given load. In this case the strain stress becomes very important from the strength of the deck, as for one that affects the strength of the deck construction, one of which is the stiffener distance. This study aims to analyze the maximum strain stress on the deck of the Ferry Ro - ro. The method used is Finite Element Method (FEM) by varying the stiffener distance in the deck construction. The research results obtained, namely the variation of the stiffener distance of 600 mm. 285.5 N/mm2 and the maximum strain released is 1.76 x 10-3 mm, at a variation of 700 mm stiffener distance the maximum stress released is 378,075 N/mm2 and the maximum strain released is 1.77 x 10-3 mm, at a stiffener distance variation 800 mm the maximum stress released is 383,737 N/mm2 and the maximum strain released is 1.78 x -3 mm, at 900 mm stiffener distance variations the maximum stress is 389,188 N/mm2 and the maximum strain released is 1.79 x 10-3 mm, at variations in distance stiffener 1000 mm the maximum stress released is 425,388 N/mm2 and the maximum strain released is 1.8 x 10 -3 mm, The value of strain increasingly increases followed by the farther distance of the stiffener equal 0.6%, and the stress value is at a variation increasingly increases followed by the farther distance of the stiffener equal 12.24%.